Evidence‐informed policymaking: Modelling nurses' career pathway from registered nurse to advanced practice nurse. Issue 1 (4th September 2019) - Jokiniemi, Krista; Suutarla, Anna; Meretoja, Riitta; Kotila, Jaana; Axelin, Anna; Flinkman, Mervi; Heikkinen, Katja; Fagerström, Lisbeth
Abstract: Aim: To formulate, validate, and disseminate policy, modelling nurses' career pathway from registered to advanced practice nurse. Method: The evidence‐informed policy and practice pathway framework was utilized. Multiple methods were used, including scoping review of literature, consultation of key informants, survey study, and expert group round‐table discussions during 5‐year project between 2013 and 2018. Results: Through (a) sourcing, (b) using, and (c) implementing the evidence, the expert group worked systematically to formulate a policy on a career pathway from registered to advanced practice nurse. The formulated career pathway includes three competence levels: registered nurse, specialized nurse, and advanced practice nurse, which includes the roles of nurse practitioner and clinical nurse specialist. In addition, validation and dissemination of the policy, as well as its effective implementation and the process of integrating it into practice, were examined. Conclusion: Evidence‐informed policymaking is an effective, interactive way to work collaboratively in achieving consensus and translating knowledge into practice. The formulated policy will contribute to the increased awareness, acknowledgement, and implementation of the registered nurses' traditional and new roles within health care environments. Implementing and integrating the policy in national health care policy, legislation, education, and organizations across the country is a work in progress. SUMMARY STATEMENT: What is already known about this topic? In the last 20 years, advanced practice nursing role development has escalated in several countries, including in Finland. Previously in Finland, there has been no description of the national‐level clinical career pathway from registered nurse to advanced practice nurse. Ensuring effective uptake and utilization of new roles requires policymaking. What this paper adds? A description of the policymaking process to model nurses' career pathway from registered to advanced practice nurse. Description of the use of the evidence‐informed policy and practice pathway framework to guide the policymaking process involving several stakeholders. The implications of this paper: The process described will be used to influence and develop national policy, modelling nurses' career pathway from registered nurse to advanced practice nurse, in an attempt to aid health care organizations to develop and optimally utilize nursing resources. The policymaking process described can be replicated in other countries developing new roles for registered nurses.